Digitalisasi Usaha Bagi Pelaku UMKM di Laban Central Park - Abdillah, Khubbi; Aristyanto, Erwan; Indradjaja, Nobella; Aulia Rachman, Fahrizal; Aulia , Nuri (Public Administration Dept, Faculty of Social and Political Science, 2024)
In the midst of the times, digitalization has proven to be one of the keys to business resilience and sustainability, especially MSMEs which are one of the business categories that have been quite hit by the COVID-19 pandemic. One of the areas in East Java that mobilizes the community of MSME actors is Laban Village, Menganti District, Gresik. Laban Central Park is a forum for many local MSME actors from Laban Village, but not many of the MSME actors have enough knowledge about business digitalization and can apply this knowledge, even though the benefits have proven to be quite large for business progress in the future. Therefore, based on the results of interviews and sharing sessions that have been conducted, a work program has been prepared to introduce or increase knowledge about business digitalization for MSME actors in Laban Village, especially in Laban Central Park. The work program is carried out with the stages of observation, socialization, and assistance to use social media and digital wallets as business tools, with the hope that participants can apply digitalization to advance their businesses. Suggestions that can be given based on the observation and implementation of activities are so that there is a follow-up or program that is implemented in the long term so that assistance for MSME actors, especially for middle-aged people, can be carried out more intensively and in detail so that they can continue to hone the abilities and habits of MSME actors in using business digitalization technology.